2002
DOI: 10.1002/1521-3773(20020104)41:1<169::aid-anie169>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-Catalyzed Oxidative Heck Reactions

Abstract: Aryl boronic acids can undergo a Heck‐type reaction catalyzed by RuII in the presence of CuII, which serves as a reoxidant in each cycle (see scheme, step 1). Compatibility with halide substituents offers attractive synthetic potential (step 2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…61,62 These investigations demonstrated that a ruthenium-carbon bond can be formed through a nucleophilic substitution and at the alkene insertion step. 63 Also, a major characteristic of ruthenium(II) chemistry is its inertness to organohalides under oxidative conditions. These features and observations may provide a promising opportunity to use ruthenium(II) complexes in the oxidative Heck reaction of haloboronic acids under reaction conditions for which it is generally impossible to effectively use palladium catalysts.…”
Section: Scheme 19mentioning
confidence: 99%
“…61,62 These investigations demonstrated that a ruthenium-carbon bond can be formed through a nucleophilic substitution and at the alkene insertion step. 63 Also, a major characteristic of ruthenium(II) chemistry is its inertness to organohalides under oxidative conditions. These features and observations may provide a promising opportunity to use ruthenium(II) complexes in the oxidative Heck reaction of haloboronic acids under reaction conditions for which it is generally impossible to effectively use palladium catalysts.…”
Section: Scheme 19mentioning
confidence: 99%
“…Unusual ruthenium-catalysed oxidative Heck reactions have also have also been studied. 187 New classes of catalyst include a ruthenium() bis(N-heterocyclic carbene)pyridine for the hydrogenation of carbonyl compounds, 188 chiral ester functionalised Cp complexes of iron(), 189 and new ferrocenyl ligands exhibiting excellent enantioselectivities for asymmetric hydrogenation of amino acid synthesis. 190 A linkage isomer of decaphenyl ferrocene has been isolated and structurally characterised and contains η 5 -C 5 Ph 5 cyclopentadienyl and η 5/6 -C 5 Ph 5 arene coordination.…”
Section: Methodsmentioning
confidence: 99%
“…The Heck reaction, pioneered by Heck and Mizoroki in the late 1960s and the early 1970s ( Heck, 1968 , Mizoroki et al., 1971 , Heck and Nolley, 1972 ), along with other cross-coupling reactions, led to a revolution in organic chemistry ( Johansson Seechurn et al., 2012 ). In the last 50 years, many types of Heck and Heck-type reactions, including metal-catalyzed ( Heck, 1968 , Mizoroki et al., 1971 , Heck and Nolley, 1972 , Littke and Fu, 2001 , Farrington et al., 2002 , Na et al., 2004 , Loska et al., 2008 , Delcamp et al., 2013 , Nishikata et al., 2013 , Standley and Jamison, 2013 ), photo-induced ( Iqbal et al., 2012 , Liu et al., 2013 , Paria et al., 2014 , Yu et al., 2014 ), or base-mediated ( Rueping et al., 2011 , Shirakawa et al., 2011 , Sun et al., 2011 ) reactions, have been elegantly developed ( Beletskaya and Cheprakov, 2000 , Dounay and Overman, 2003 , Wu et al., 2010 , Le Bras and Muzart, 2011 , Mc Cartney and Guiry, 2011 , Tang et al., 2015 ). Notwithstanding these classical reaction modes, there is no precedent of Brønsted acid-catalyzed or Brønsted acid-promoted Heck (or type) reaction being realized.…”
Section: Introductionmentioning
confidence: 99%